2000
DOI: 10.1152/ajpheart.2000.278.3.h714
|View full text |Cite
|
Sign up to set email alerts
|

Altered L-type Ca2+ channel currents in vascular smooth muscle cells from experimental diabetic rats

Abstract: Vascular complications of diabetes are associated with abnormal Ca(2+) handling by vascular smooth muscle cells (SMCs) in which the alteration in L-type voltage-dependent Ca(2+) channel (VDCC) currents may play an important role. In the present study, the characteristics of L-type VDCC currents in tail artery SMCs from streptozotocin-induced diabetic rats were examined. The densities, but not the voltage dependence, of L-type VDCC currents were reduced as diabetes progressed from 1 wk to 3 mo. The inhibitory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 27 publications
1
42
0
2
Order By: Relevance
“…In type 1 diabetic rats, the L-type Ca 2ϩ channels in vascular smooth muscle cells showed increased sensitivity to cAMP and hyperglycemia (36), and BK channel sensitivity to carbon monoxide is reduced (37). In addition, after 24 h of exposure to high glucose (23 mmol/l), rat coronary smooth muscle cells showed impaired activity in the voltage-gated K ϩ channels (4-aminopyridine sensitive) (38).…”
Section: Discussionmentioning
confidence: 99%
“…In type 1 diabetic rats, the L-type Ca 2ϩ channels in vascular smooth muscle cells showed increased sensitivity to cAMP and hyperglycemia (36), and BK channel sensitivity to carbon monoxide is reduced (37). In addition, after 24 h of exposure to high glucose (23 mmol/l), rat coronary smooth muscle cells showed impaired activity in the voltage-gated K ϩ channels (4-aminopyridine sensitive) (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that KCl depolarisation-induced changes in [Ca 2+ ] i and contractions are diminished in both macrovascular and microvascular smooth muscle cells from diabetic rats [27,28,29,30,31] and this is thought to occur through a reduction in the density of voltage-dependent L-type Ca 2+ channels [32] (VDCC). In our study, the action of high K + was maintained in the retinal MVSM cells from diabetic rats suggesting that neither the VDCCs themselves nor their activation require- PKC activation (PMA).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors showed that in skeletal muscle cells the effectiveness of DHP under short-term application is regulated by Ca 2+ and different second messengers [11]. Others reported the changes in pharmacological sensitivity of HVA calcium channels to DHP [28].…”
Section: Discussionmentioning
confidence: 99%